2012 IEEE International Conference on Condition Monitoring and Diagnosis 2012
DOI: 10.1109/cmd.2012.6416349
|View full text |Cite
|
Sign up to set email alerts
|

The electric field distribution in oil-paper insulation under combined AC-DC voltage

Abstract: The valve winding in the converter transformer withstands several types of voltage, including the AC, DC, and the combined AC-DC voltage. It is important to consider the effects of voltage type to the electric field distribution. In this paper, a combined AC-DC source was constructed. The electric field distribution of oil paper insulation model was measured by Kerr electro-optic effect, under combined AC-DC voltage with different composite ratios of DC/AC. The results indicate that: 1) DC electric field distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In general, the dielectric coefficient of insulating paper is 4 to 5, while that of insulating oil is about 2.2. Under the action of the electric field, the field intensity shared in composite insulation is inversely proportional to the dielectric coefficient of the material (Wu et al 2012). Improving the oil absorption rate of insulating paper is beneficial to the distribution of electric field intensity.…”
Section: Effect Of Cnc On the Oil Absorption Rate Of Insulating Papermentioning
confidence: 99%
“…In general, the dielectric coefficient of insulating paper is 4 to 5, while that of insulating oil is about 2.2. Under the action of the electric field, the field intensity shared in composite insulation is inversely proportional to the dielectric coefficient of the material (Wu et al 2012). Improving the oil absorption rate of insulating paper is beneficial to the distribution of electric field intensity.…”
Section: Effect Of Cnc On the Oil Absorption Rate Of Insulating Papermentioning
confidence: 99%
“…It is generally used for the measurement of ground-level electromagnetic environment, and the stability is poor in strong electric field environment. Optical electric field sensors mainly include electric field sensors based on the Pockels effect (Zeng et al, 2013;Yang et al, 2015;Aristizabal-Tique et al, 2020) and the Kerr effect (Wu et al, 2012;Qi et al, 2016), which are highly priced and the sensitivity is greatly affected by frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on the creepage discharge characteristics of oil-paper insulation under ADCV focus mainly on two aspects: (1) they investigate the factors affecting creepage discharge, including different voltage types and electric field components [4], discharge characteristics [5][6][7][8], aging [9,10], and other factors. It has been revealed that the temperature rise, aging, and DC electric field components accelerate the creepage discharge development and (2) they intend to mainly find the characteristic parameters and recognition methods that can effectively characterize the creepage discharge development under ADCV.…”
Section: Introductionmentioning
confidence: 99%